SARS-CoV-2 RNA in wastewater anticipated COVID-19 occurrence in a low prevalence area. (15th August 2020) - Randazzo, Walter; Truchado, Pilar; Cuevas-Ferrando, Enric; Simón, Pedro; Allende, Ana; Sánchez, Gloria
Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused more than 200, 000 reported COVID-19 cases in Spain resulting in more than 20, 800 deaths as of April 21, 2020. Faecal shedding of SARS-CoV-2 RNA from COVID-19 patients has extensively been reported. Therefore, we investigated the occurrence of SARS-CoV-2 RNA in six wastewater treatments plants (WWTPs) serving the major municipalities within the Region of Murcia (Spain), the area with the lowest COVID-19 prevalence within Iberian Peninsula. Firstly, an aluminum hydroxide adsorption-precipitation concentration method was validated using a porcine coronavirus (Porcine Epidemic Diarrhea Virus, PEDV) and mengovirus (MgV). The procedure resulted in average recoveries of 10 ± 3.5% and 10 ± 2.1% in influent water (n = 2) and 3.3 ± 1.6% and 6.2 ± 1.0% in effluent water (n = 2) samples for PEDV and MgV, respectively. Then, the method was used to monitor the occurrence of SARS-CoV-2 from March 12 to April 14, 2020 in influent, secondary and tertiary effluent water samples. By using the real-time RT-PCR (RT-qPCR) Diagnostic Panel validated by US CDC that targets three regions of the virus nucleocapsid (N) gene, we estimated quantification of SARS-CoV-2 RNA titers in untreated wastewater samples of 5.4 ± 0.2 log10 genomic copies/L on average. Two secondary water samples resulted positive (2 out of 18) and all tertiary water samples tested as negative (0 out 12). This environmental surveillance data were compared to declared COVID-19 cases at municipality level, revealing that members of the community were shedding SARS-CoV-2 RNA in their stool even before the first cases were reported by local or national authorities in many of the cities where wastewaters have been sampled. The detection of SARS-CoV-2 in wastewater in early stages of the spread of COVID-19 highlights the relevance of this strategy as an early indicator of the infection within a specific population. At this point, this environmental surveillance could be implemented by municipalities right away as a tool, designed to help authorities to coordinate the exit strategy to gradually lift its coronavirus lockdown. Graphical abstract: Image 1 Highlights: An adsorption-precipitation concentration method was validated using a porcine coronavirus. First detection of SARS-CoV-2 RNA in untreated wastewater in Spain. 11% secondary treated water samples tested positive for at least one SARS-CoV-2 RT-qPCR target. None of the tertiary effluent samples (n = 12) tested positive for SARS-CoV-2. SARS-CoV-2 RNA was detected in wastewater before the first COVID-19 cases were declared by local authorities.